Jak-Stat Signaling Pathway Related Gene Expressions and Blood Biochemical indicators in Acute Promyelocytic Leukemia - Kieu Trang, Bui; Thi Xuan, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2020)
Acute promyelocytic leukemia (APL) is a type of acute leukemia, which has the highest death rate among blood cancers and caused by a specific (15; 17) chromosomal translocation, resulting in a fusion gene PML/RARα. Klotho gene plays a role in preventing aging, inflammation and cancer. CTLA4, PD1 and LAG3 are immunosuppressive receptors located on surface of T cells and considered as a negative regulation of immune response. These genes regulate immune cell activity through several signalling moleculars such as STATs and NF-κB. In this study, to additionally determine the difference between APL and other leukemia, we performed experiments to measure mRNA expression of above genes by using realtime-PCR. Results showed that mRNA levels of KL, CTLA4, PD1 and LAG3 genes were lower, while expressions of STAT1, STAT3, STAT5 and STAT6 genes were significantly higher in APL patients than healthy controls. In addition, IκB-α gene expression was unaltered on APL cells. The results of this study would partially contribute to an understanding of the differences in JAK-STAT signaling associated gene expressions between APL and other leukemia groups. This is important to apply for effective chemotherapy for each type of leukemia. Keywords Acute promyelocytic leukemia, klotho, CTLA4, IκB-α, LAG3, PD1, STAT. References [1] M. Gianni, M. Terao, I. Fortino, M. LiCalzi, V. Viggiano, T. Barbui, A. Rambaldi, E. Garattini, Stat1 is induced and activated by all-trans retinoic acid in acute promyelocytic leukemia cells, Blood, 89 (1997) 1001-1012. [2] A. Kohlmann, C. Schoch, M. Dugas, S. Rauhut, F. Weninger, S. Schnittger, W. Kern, T. Haferlach, Pattern robustness of diagnostic gene expression signatures in leukemia, Genes, chromosomes & cancer, 42 (2005) 299-307. [3] C.B. Leibrock, J. Voelkl, O.M. Kuro, F. Lang, U.E. Lang, 1,25(OH)2D3 dependent overt hyperactivity phenotype in klotho-hypomorphic mice, Scientific reports, 6 (2016) 24879. [4] D. Skrajnowska, B. Bobrowska-Korczak, A. Tokarz, Disorders of Mechanisms of Calcium Metabolism Control as Potential Risk Factors of Prostate Cancer, Current medicinal chemistry, 24 (2017) 4229-4244. [5] V. Delcroix, O. Mauduit, N. Tessier, A. Montillaud, T. Lesluyes, T. Ducret, F. Chibon, F. Van Coppenolle, S. Ducreux, The Role of the Anti-Aging Protein Klotho in IGF-1 Signaling and Reticular Calcium Leak: Impact on the Chemosensitivity of Dedifferentiated Liposarcomas, 10 (2018). [6] M. Azuma, D. Koyama, J. Kikuchi, H. Yoshizawa, D. Thasinas, K. Shiizaki, M. Kuro-o, Y. Furukawa, E. Kusano, Promoter methylation confers kidney-specific expression of the Klotho gene, FASEB journal : official publication of the Federation of American Societies for Experimental Biology, 26 (2012) 4264-4274. [7] E.L. Masteller, E. Chuang, A.C. Mullen, S.L. Reiner, C.B. Thompson, Structural analysis of CTLA-4 function in vivo, Journal of immunology (Baltimore, Md. : 1950), 164 (2000) 5319-5327. [8] B.T. Fife, J.A. Bluestone, Control of peripheral T-cell tolerance and autoimmunity via the CTLA-4 and PD-1 pathways, Immunological reviews, 224 (2008) 166-182. [9] L.P. Andrews, A.E. Marciscano, C.G. Drake, D.A. Vignali, LAG3 (CD223) as a cancer immunotherapy target, Immunological reviews, 276 (2017) 80-96. [10] B. Huard, P. Prigent, M. Tournier, D. Bruniquel, F. Triebel, CD4/major histocompatibility complex class II interaction analyzed with CD4- and lymphocyte activation gene-3 (LAG-3)-Ig fusion proteins, European journal of immunology, 25 (1995) 2718-2721. [11] F. Xu, J. Liu, D. Liu, B. Liu, M. Wang, Z. Hu, X. Du, L. Tang, F. He, LSECtin expressed on melanoma cells promotes tumor progression by inhibiting antitumor T-cell responses, Cancer research, 74 (2014) 3418-3428. [12] J. Kotaskova, B. Tichy, M. Trbusek, H.S. Francova, J. Kabathova, J. Malcikova, M. Doubek, Y. Brychtova, J. Mayer, S. Pospisilova, High expression of lymphocyte-activation gene 3 (LAG3) in chronic lymphocytic leukemia cells is associated with unmutated immunoglobulin variable heavy chain region (IGHV) gene and reduced treatment-free survival, The Journal of molecular diagnostics: JMD, 12 (2010) 328-334. [13] P. Aigner, T. Mizutani, J. Horvath, T. Eder, STAT3beta is a tumor suppressor in acute myeloid leukemia, 3 (2019) 1989-2002. [14] C. Schubert, M. Allhoff, S. Tillmann, T. Maie, I.G. Costa, D.B. Lipka, M. Schemionek, K. Feldberg, J. Baumeister, T.H. Brummendorf, N. Chatain, S. Koschmieder, Differential roles of STAT1 and STAT2 in the sensitivity of JAK2V617F- vs. BCR-ABL-positive cells to interferon alpha, Journal of hematology & oncology, 12 (2019) 36. [15] T. Bowman, R. Garcia, J. Turkson, R. Jove, STATs in oncogenesis, Oncogene, 19 (2000) 2474-2488. [16] C. Gasparini, C. Celeghini, L. Monasta, G. Zauli, NF-kappaB pathways in hematological malignancies, Cellular and molecular life sciences : CMLS, 71 (2014) 2083-2102. [17] S. Prasad, J. Ravindran, B.B. Aggarwal, NF-kappaB and cancer: how intimate is this relationship, Molecular and cellular biochemistry, 336 (2010) 25-37. [18] N. Erfani, S.M. Mehrabadi, M.A. Ghayumi, M.R. Haghshenas, Z. Mojtahedi, A. Ghaderi, D. Amani, Increase of regulatory T cells in metastatic stage and CTLA-4 over expression in lymphocytes of patients with non-small cell lung cancer (NSCLC), Lung cancer (Amsterdam, Netherlands), 77 (2012) 306-311. [19] K.V. Shah, A.J. Chien, C. Yee, R.T. Moon, CTLA-4 is a direct target of Wnt/beta-catenin signaling and is expressed in human melanoma tumors, The Journal of investigative dermatology, 128 (2008) 2870-2879. [20] S. Salvi, V. Fontana, S. Boccardo, D.F. Merlo, E. Margallo, S. Laurent, A. Morabito, E. Rijavec, M.G. Dal Bello, M. Mora, G.B. Ratto, F. Grossi, M. Truini, M.P. Pistillo, Evaluation of CTLA-4 expression and relevance as a novel prognostic factor in patients with non-small cell lung cancer, Cancer immunology, immunotherapy : CII, 61 (2012) 1463-1472. [21] M. Grzywnowicz, J. Zaleska, D. Mertens, W. Tomczak, P. Wlasiuk, K. Kosior, A. Piechnik, A. Bojarska-Junak, A. Dmoszynska, K. Giannopoulos, Programmed death-1 and its ligand are novel immunotolerant molecules expressed on leukemic B cells in chronic lymphocytic leukemia, PloS one, 7 (2012) e35178. [22] L. Long, X. Zhang, F. Chen, Q. Pan, P. Phiphatwatchara, Y. Zeng, H. Chen, The promising immune checkpoint LAG-3: from tumor microenvironment to cancer immunotherapy, Genes & cancer, 9 (2018) 176-189. [23] R.R. Saleh, P. Peinado, J. Fuentes-Antras, P. Perez-Segura, A. Pandiella, E. Amir, A. Ocana, Prognostic Value of Lymphocyte-Activation Gene 3 (LAG3) in Cancer: A Meta-Analysis, Frontiers in oncology, 9 (2019) 1040. [24] H.A. Jensen, H.B. Yourish, R.P. Bunaciu, J.D. Varner, A. Yen, Induced myelomonocytic differentiation in leukemia cells is accompanied by noncanonical transcription factor expression, FEBS open bio, 5 (2015) 789-800. [25] B. Kovacic, D. Stoiber, R. Moriggl, E. Weisz, R.G. Ott, R. Kreibich, D.E. Levy, H. Beug, M. Freissmuth, V. Sexl, STAT1 acts as a tumor promoter for leukemia development, Cancer cell, 10 (2006) 77-87. [26] V. Gouilleux-Gruart, F. Gouilleux, C. Desaint, J.F. Claisse, J.C. Capiod, J. Delobel, R. Weber-Nordt, I. Dusanter-Fourt, F. Dreyfus, B. Groner, L. Prin, STAT-related transcription factors are constitutively activated in peripheral blood cells from acute leukemia patients, Blood, 87 (1996) 1692-1697. [27] R.M. Weber-Nordt, C. Egen, J. Wehinger, W. Ludwig, V. Gouilleux-Gruart, R. Mertelsmann, J. Finke, Constitutive activation of STAT proteins in primary lymphoid and myeloid leukemia cells and in Epstein-Barr virus (EBV)-related lymphoma cell lines, Blood, 88 (1996) 809-816. [28] H.A. Bruns, M.H. Kaplan, The role of constitutively active Stat6 in leukemia and lymphoma, Critical reviews in oncology/hematology, 57 (2006) 245-253. [29] B.H. Li, X.Z. Yang, P.D. Li, Q. Yuan, X.H. Liu, J. Yuan, W.J. Zhang, IL-4/Stat6 activities correlate with apoptosis and metastasis in colon cancer cells, Biochemical and biophysical research communications, 369 (2008) 554-560. [30] N. Carlesso, D.A. Frank, J.D. Griffin, Tyrosyl phosphorylation and DNA binding activity of signal transducers and activators of transcription (STAT) proteins in hematopoietic cell lines transformed by Bcr/Abl, The Journal of experimental medicine, 183 (1996) 811-820. [31] S.K. Chai, G.L. Nichols, P. Rothman, Constitutive activation of JAKs and STATs in BCR-Abl-expressing cell lines and peripheral blood cells derived from leukemic patients, Journal of immunology (Baltimore, Md.: 1950), 159 (1997) 4720-4728. [32] K. Shuai, J. Halpern, J. ten Hoeve, X. Rao, C.L. Sawyers, Constitutive activation of STAT5 by the BCR-ABL oncogene in chronic myelogenous leukemia, Oncogene, 13 (1996) 247-254.